Evidence-Based Policing as a Foundational Policing Model for the INP - de Fretes, Yobhel Levic; Bayunarendro, Muhammad Krisna; Cornelia, Hillary (Jurnal Ilmu Kepolisian, 2024)
In the midst of various challenges of policing and its consequences on public trust, a number of studies have examined the duties of the Police, especially the Republic of Indonesia National Police (INP), in maintaining security and public order, enforcing the law, protecting the public, and serving the community. Several contemporary policing models, such as Community Policing or Problem-Oriented Policing, have been suggested and implemented by the INP, although the parameters of its successful implementation continue to be a questionable issue. This article discusses how the concept of Evidence-Based Policing (EBP) – a new paradigm in policing – can better serve as a foundation for the Police in dealing with societal and criminal issues. EBP emphasises scientific and evidence-based decision-making, enabling officers to avoid the biases that are frequently criticised in policing practices. By utilising literature review and document analysis methods, this article examines existing policing models and demonstrates the importance of evidence-based approaches in improving INP performance. It also highlights the importance of consulting and collaborating with pracademics and international institutions that have successfully implemented EBP, in order to increase the accountability and responsibility of the INP in implementing EBP. The implementation of EBP is expected to lead to positive changes in policing culture – providing more effective and comprehensive solutions based on data and scientific studies to address crime and social problems in the community.